2021
DOI: 10.1111/1750-3841.15920
|View full text |Cite
|
Sign up to set email alerts
|

Modeling relationship between protein oxidation and denaturation and texture, moisture loss of bighead carp (Aristichthys Nobilis) during frozen storage

Abstract: To evaluate the effects of protein oxidation and denaturation on the fish texture and moisture loss during frozen storage, we measured the changes of protein oxidation and denaturation (salt-soluble protein (SSP), total sulfhydryl (SH), disulfide (SS), carbonyl contents and Ca 2+ -ATPase activity), texture (hardness), and moisture loss (drip loss) of bighead carp fillets stored at −12, −20 and −28 • C during 16 weeks. These data were employed to develop partial least squares regression (PLSR) model, radial bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Differently, the content of SSP, Ca 2+ -ATPase, and SH were all significantly decreased under frozen storage as shown above. The Pearson's positive correlations of SSP, Ca 2+ -ATPase, and SH further demonstrated the disruption of common carp protein integrity and the positive association between protein solubility and structure integrity [62,63].…”
Section: Total Sulfhydryl (Sh) Contentmentioning
confidence: 80%
“…Differently, the content of SSP, Ca 2+ -ATPase, and SH were all significantly decreased under frozen storage as shown above. The Pearson's positive correlations of SSP, Ca 2+ -ATPase, and SH further demonstrated the disruption of common carp protein integrity and the positive association between protein solubility and structure integrity [62,63].…”
Section: Total Sulfhydryl (Sh) Contentmentioning
confidence: 80%
“…(Li et al, 2020a). To assess the effect of protein oxidation on fish texture during frozen storage, Lu et al (2021) found that there was a linear relationship between protein oxidation (salt-soluble protein, total sulfhydryl, disulfide, carbonyl content and Ca2+-ATPase activity) and texture (firmness) of bighead carp fillets.…”
Section: Texturementioning
confidence: 99%